Kemampuan Berpikir Kreatif Siswa SMA dalam Memecahkan Masalah SPLTV dengan Memanfaatkan ChatGPT - Elita Nathania Dewi; Tatag Yuli Eko Siswono (Universitas Negeri Surabaya, 2026)
Creative thinking is the ability to generate new ideas in order to solve a problem. Several studies indicate that students' creative thinking skills in problem solving are still relatively low, requiring a more innovative approach. The use of Artificial Intelligence (AI) as a creative partner is considered to have the potential to support students' idea exploration and creative thinking skills in problem solving. This research is a qualitative study with the aim of describing the creative thinking skills of high school students with high, medium, and low abilities in solving SPLTV problems using ChatGPT. This research was conducted at State High School 14 in Surabaya with a subjects of six students, comprising two students with high abilities, two students with moderate abilities, and two students with low abilities. The research data was obtained through a mathematics ability test, SPLTV problem-solving tests utilizing ChatGPT, and interviews. To ensure the validity of the research data obtained, source triangulation was carried out. The results showed that students with high abilities can fulfill all three aspects of creative thinking ability indicators. Students with moderate abilities fulfill the aspects of fluency and flexibility. Students with low abilities only fulfill the aspect of fluency. Overall, students with high, moderate, and low abilities can only use ChatGPT to evaluate ideas and solutions that they already have. Thus, the use of ChatGPT in mathematics learning does not automatically support students' creative thinking abilities optimally, but depends on clear guidelines for using ChatGPT and a good understanding of ChatGPT.